Assaut du discours straight et universalisation du point de vue minoritaire dans les essais de Monique Wittig - Claire Michard (Genre, Sexualité et Société)
This text points out how the discursive strategies used by Monique Wittig in her essays destroy the claim to universality of the straight thinking based on the political system of heterosexuality, and, simultaneously, construct the author’s particular point of view as universal.